Análise teórica-experimental de semicondutores / Mateus Meneghetti Ferrer - Ferrer, Mateus Meneghetti (2016)
The rapid modernization of industrial and technological poles spurs the development of new materials, always in search of efficiency and low costs, given that the expression "new materials" does not relate just to the new classes or compounds never seen before but also to the structural modifications in materials already studied. In this context, research using theoretical and experimental models tends Researches using combined theoretical and experimental methods tend to be more and more commonly due to the better correlation between system characteristics and properties. However, a better interpretation can assists in the planning and developing of new materials. In the present study, a set of theoretical and experimental models were built in order to explain the properties and phenomena of semiconductors. The chosen materials were the α-Ag2WO4, β-Ag2MoO4, Co3O4, α- Fe2O3 and In2O3. Characterization techniques of X-Ray difraction, Rietveld refinament, Raman spectroscopy, scanning electron microscopy and transmission electron microscopy were related with quantum mechanical calculations to a better understanding of the observed results. Theoretical results of band structure and density of states are in agreement with the experimental band gaps.The data showed a creation of new eletronic states on the forbiden region on the band gap due to the criation of structural defects, by means of a impurity or structural changes. The final models were used to a better explanation of the photoluminescent properties modifications. Quantum mechanical calculations were also used to the explanation of a phenomenon caused by electron bombing, which was observed in Ag2WO4 and Ag2MoO4 crystals. In this model, the Ag reduction results in its removal of the clusters generating the Ag metallic filaments on the material surface. Finally, it was created a new approach about the mapping and prediction of crystals morphology that serves as an experimental reference to the comparison between surface and final properties. The presented papers consist in an interdisciplinary research, from fundamental to applications and show how quantum chemical and other theoretical computational means can be used for an understanding of physical and chemical properties of materials for searching a rational materials design.